(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Interactive and collaborative learning in ‘live’ and online (synchronous and asynchronous) environments generates an influence on the perception, motivation and outcomes of learning among students. From that theory, the aim of this contribution is to analyse the effects of different teaching approaches unexpectedly provoked by the COVID-19 pandemic. The object of this study is a master’s course titled “History and Education” of which half the classes were taught via synchronous live lectures in an interactive and collaborative group condition and half via asynchronous digital modules to be individually completed without interaction or collaboration. The effects of those different conditions on students’ perception of the comprehensibility and ease of studying the course, on students’ interest, motivation and efforts, and on their learning performance was examined via a descriptive and exploratory case study using a questionnaire and the outcomes of a written examination. In the questionnaire, the course students had to score both conditions for several issues and explain their scores. The results show that the live lectures obtained better average scores than the digital modules, except for the perception of the ease of studying the course. Also, more students attributed higher scores to the live lectures on each issue, again except for the perception of the ease of studying the course. The learning performances did not generate differences between the two conditions. These results are discussed within the existing research and reflected upon in the light of the continuous pandemic forcing higher education to combine different shapes of teaching.